Analysis of Literacy Ability and Mathematical Problem-Solving Ability reviewed from Student Self-Efficacy - Nurma Izzati; Muhammad Agung Febriyanto (Universitas Teknokrat Indonesia, 2026)
The low levels of mathematical literacy and problem-solving skills among Indonesian students, as reflected in the 2022 PISA results, underscore the need for an in-depth study of the factors influencing these two skills, one of which is self-efficacy. This study aims to describe the characteristics of students’ mathematical literacy and mathematical problem-solving skills in relation to their level of self-efficacy. The study employed a qualitative method with a descriptive approach. The research subjects consisted of 26 eighth-grade students from Class VIII G at MTs Negeri 3 Cirebon, selected through purposive sampling; subsequently, three students were chosen based on high, moderate, and low self-efficacy categories. Data collection was conducted using a mathematical literacy test instrument, a mathematical problem-solving test instrument, and a self-efficacy questionnaire. Data analysis utilized the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions, and its validity was tested through triangulation of methods and sources. The results of the study indicate that students with high self-efficacy possess excellent mathematical literacy and problem-solving skills across nearly all indicators. Students with moderate self-efficacy exhibited an asymmetrical profile, showing weaknesses in the stages of understanding and formulating problems, yet strength in the planning and strategy implementation stages. Students with low self-efficacy demonstrated low ability across all indicators, with the most fundamental weaknesses in the stages of formulating problems and reviewing solution results. There is a consistent trend that the higher a student’s self-efficacy, the better their mathematical literacy and problem-solving skills. The problem-formulation and problem-understanding stages consistently emerge as the weakest points across all self-efficacy categories, thus requiring priority in the design of mathematics instruction.